The use of Finding Nemo Movie to Improve Vocabulary Mastery of the Seventh Grade Students of SMPN 17 Semarang in Academic Year 2023/2024 - Siti Nur Zulaihah; Jafar Sodiq; Arso Setyaji (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the effectiveness of using the